Sequential cardiovascular magnetic resonance assessment of left ventricular ejection fraction for prediction of subsequent events in a large multicenter STEMI registry. (13th July 2021) - Gavara, J; Marcos-Garces, V; Rios-Navarro, C; Lopez-Lereu, MP; Monmeneu, JV; Bonanad Lozano, C; Moratal, D; Chorro, FJ; Valente, F; Lorenzatti, D; Rodriguez-Palomares, JF; Ortiz-Perez, JT; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This work was supported by "Instituto de Salud Carlos III" and "Fondos Europeos de Desarrollo Regional FEDER" Background. Cardiovascular magnetic resonance (CMR) is the best tool for left ventricular ejection fraction (LVEF) quantification, but as yet the prognostic value of sequential LVEF assessment for major adverse cardiac event (MACE) prediction after ST-segment elevation myocardial infarction (STEMI) is uncertain. Purpose. We explored the prognostic impact of sequential assessment of CMR-derived LVEF after STEMI to predict subsequent MACE. Methods. We recruited 1036 STEMI patients in a large multicenter registry. LVEF (reduced [r]: <40%; mid-range [mr]: 40-49%; preserved [p]: ≥50%) was sequentially quantified by CMR at 1 week and after >3 months of follow-up. MACE was regarded as cardiovascular death or re-admission for acute heart failure after follow-up CMR. Results. During a 5.7-year mean follow-up, 82 MACE (8%) were registered. The MACE rate was higher only in patients with LVEF < 40% at follow-up CMR (r-LVEF 22%, mr-LVEF 7%, p-LVEF 6%; p-value < 0.001). Based on LVEF dynamics from 1-week to follow-up CMR, incidence of MACE was 5% for sustained LVEF³40% (n = 783), 13% for improved LVEF (from <40 to ³40%, n = 96), 21% for worsened LVEF (from ³40% to <40%, n = 34) and 22% for sustained LVEF <40% (n = 100), p-value < 0.001. Using a Markov approach that considered all studies performed, transitions towards improved LVEF predominated and only r-LVEF (at any time assessed) was significantly related to higher incidence of subsequent MACE. Conclusions. LVEF constitutes a pivotal CMR index for simple and dynamic post-STEMI risk stratification. Detection of reduced LVEF (<40%) by CMR at any time during follow-up identifies a small subset of patients at high risk of subsequent events.